Nuremberg Trials (Harvard Law School Library's Nuremberg Trials Project)
The Harvard Law School Library's Nuremberg Trials Project is an open-access initiative to create and present digitized images and full-text versions of the Library's Nuremberg Trials documents, descriptions of each document, and general information about the trials. The project provides access to the documentary record and other associated materials for all thirteen trials. We currently offer page images and searchable document descriptions for all documents as well as searchable full-text versions for most prosecution exhibits and most of the trial transcripts. Both prosecution and trial exhibits as well as all trial transcripts are currently only offered in the English-language versions used at the time of the Trials. Important: when citing from documents and transcripts, always verify the exact wording by consulting the accompanying page images of the document in question. The full-text versions of transcripts and documents are a product of human- and computer-aided transcription and may deviate in small ways from the originals.
Keywords: _open access

The EHRI Portal. Documents d'archives concernant l'Holocauste (The EHRI Portal)
The EHRI portal offers access to information on Holocaust-related archival material held in institutions across Europe and beyond.